Invention, Innovation and Innovative practices - Joshi, Manoj (Journal of Entrepreneurship, Business and Economics, 2017)
Invention may be described as an action towards creating something new, typically a process or a device.' Innovation is described as an idea and its outcome interpreted as new by individuals and also seen as a multiple application of invention. Innovators are individuals who carry out innovation, create most of the wealth, new or a proportionate jump from the existing, while others tend to safeguard it. Much of the growth comes from innovators who may also be entrepreneurs (Gartner, 1989) leading to creation of employment. These innovators and even entrepreneurs bestow new value to old assets. Create entirely new fountains of wealth. Take the Indian example of Flipkart, Inmobi, Quikr, Olacabs, Paytm, Oyo rooms and many more who have created wealth with barely any base. Many large companies have also been successful in creation of wealth, like the Wipro, Bharti Telecom, TCS and many more companies of its kind. This wealth creation trend is similar around the world. Most of these Innovative companies have experienced the continuous challenge of volatility, uncertainty, complexity and ambiguity (VUCA) environment. The question is if innovation & entrepreneurship is restricted to start-ups? Some larger companies do also engage in creation of wealth and that is the basis of their profitable existence. Thus it is necessary to examine the factors why some companies are able to create more wealth and value than others! Why certain nations do better than others and what is the underlying cause for such successes in creation of wealth? Research paper Keywords: Invention, Innovation, Innovative practices, entrepreneurship, VUCA Reference to this paper should be made as follows: Joshi, M. (2017). Invention, Innovation and Innovative practices: a reason to study in a VUCA perspective, Journal of Entrepreneurship, Business and Economics , 5 (2), 87–109.